FRI0201 Analysis of infection risk in patients with limited return of peripheral B cells after a period of 2 years or more following any rituximab treatment course in RA clinical trials. (23rd January 2014) - Mease, P.; van Vollenhoven, R.; Durez, P.; Sheeran, T.; Dougados, M.; Gόmez-Reino, J.J.; Tyson, N.; Mehbob, A.; Lehane, P.B.
Abstract : Objectives: To evaluate the infection risk and long-term safety of prolonged peripheral CD19+ B cell depletion (BCD) following rituximab (RTX) treatment in RA clinical trials. Methods: Subgroups of patients (pts) with peripheral BCD from the RTX All Exposure population were analysed. Infection rates (from first RTX exposure until last valid observation, including safety follow-up) were compared to overall infection rates in "All Exposed" and "anti-TNF inadequate responder (TNF-IR)" pts. During the 2 yr period of BCD, pts did not receive additional RTX therapy, although some pts were subsequently retreated. B cell (CD19+) levels were measured every 4-12 wks, depending on clinical study protocol. Results: As of Sep 2010, 3194 pts (All Exposure) had been treated with RTX (11962 patient-yrs [PY]), of whom 41% (n=1324) were TNF-IR pts. Limited return of peripheral B cells (defined as CD19 count less than lower limit of normal [LLN; <80 cells/μL] ≥2 yrs after any RTX course) occurred in 345/3194 pts (11%); 92 of these pts had CD19+ below lower limit of quantification (LLQ; <20 cells/μL) for ≥2 yrs. Pts with low CD19 for ≥2 yrs had lower circulating mean CD19 (123 cells/μL, with 35% pts <LLN) before RTX treatment. At baseline, these pts were on average older, had longer disease duration, higher disease activity, greater number of past DMARDs and oral corticosteroid use vs All Exposure, suggesting these pts may have higher a priori risk of developing serious infection (SIE). Infection rates/100 PY were lower in pts with low CD19 for ≥2 yrs vs All Exposure and TNF-IR pts (Table ). SIE rates in pts were similar to other populations (overlapping 95% CIs) and were most comparable to TNF-IR pts (RTX-indicated population). There were no apparent differences in types or outcomes of SIEs and no opportunistic infections were reported during prolonged BCD. B-cell depletion/repletion patterns varied; however, many pts remained B cell depleted through multiple treatment courses, with no additional safety concerns observed. Conclusions: This analysis of 345 pts with limited return of peripheral CD19+ B cells ≥2 yrs after any RTX treatment course showed no clear association with an increased risk of infections, including SIEs. Limitations include low patient numbers (n=92) in the subgroup with CD19 < LLQ, therefore data comparisons should be interpreted with caution. Rates and infection profiles were comparable to other pts who received RTX, with baseline disease characteristics and SIE rates most closely resembling that of the anti-TNF IR population. Disclosure of Interest: P. Mease Grant/Research support from: Abbott, Amgen, Biogen-Idec, BMS, Genentech, Janssen, Lilly, Merck, Novartis, Pfizer, Roche, UCB, Consultant for: Abbott, Amgen, Biogen-Idec, BMS, Genentech, Janssen, Lilly, Merck, Novartis, Pfizer, Roche, UCB, Speakers Bureau: Abbott, Amgen, Biogen-Idec, BMS, Genentech, Janssen, Lilly, Pfizer, Roche, UCB, R. van Vollenhoven Grant/Research support from: Abbott, GSK, Merck, Pfizer, Roche, UCB, Consultant for: Abbott, GSK, Merck, Pfizer, Roche, UCB, P. Durez Speakers Bureau: BMS, Pfizer, Merck, Abbott, Roche, UCB, T. Sheeran Grant/Research support from: Roche, Abbott, Novartis, GSK, Speakers Bureau: Roche, M. Dougados Grant/Research support from: Roche, Abbott, Pfizer, BMS, UCB, Novartis, Merck, Consultant for: Roche, Abbott, Pfizer, BMS, UCB, Novartis, Merck, J. Gόmez-Reino Grant/Research support from: MSD, UCB, Consultant for: MSD, Pfizer, Roche, UCB, Speakers Bureau: MSD, Pfizer, Roche, N. Tyson Shareholder of: Roche Products Ltd, Employee of: Roche Products Ltd, A. Mehbob Employee of: Roche Products Ltd, P. Lehane Employee of: Roche Products Ltd